2021
DOI: 10.22487/25411969.2021.v10.i1.15466
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of boosting on the C5.0 algorithm in the health development index data

Abstract: The public health development index is a collection of health indicators that can be easily and directly measured to describe health problems down to the district/city level. The last calculation of the public health development index in Indonesia was carried out in 2018 with the result that not all districts/cities are in a high condition. This research was conducted to classify districts/cities that have a high and low public health development index using the boosted C5.0 algorithm. The results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The results showed that the model's accuracy increased with 60 iterations, with a relatively small error in the 10th iteration. The final accuracy, sensitivity, and specificity obtained were 97.09%, 96.72%, and 97.62%, respectively (Fajri et al, 2021). The difference between the author's research and previous studies is a different dataset.…”
Section: Introductionmentioning
confidence: 73%
“…The results showed that the model's accuracy increased with 60 iterations, with a relatively small error in the 10th iteration. The final accuracy, sensitivity, and specificity obtained were 97.09%, 96.72%, and 97.62%, respectively (Fajri et al, 2021). The difference between the author's research and previous studies is a different dataset.…”
Section: Introductionmentioning
confidence: 73%
“…In this study, the C5.0 Algorithm Method will be used with the application of this method [9], [10], the author can determine how satisfied or dissatisfied students are in carrying out the online teaching and learning process during the Covid 19 pandemic [11]. That way the school will take a policy or action in the offline or online learning process by dividing the time for class entry at the Simalungun University Foundation Tourism Vocational School.…”
Section: Introductionmentioning
confidence: 99%